(untitled) (Herald of Journalism, 2018)
The article deals with technology advancements in social media, marketing tools of the PR practitioner. The authors describe the basic requirements for textual and visual information in social networks for effective promotion, as well as analysis of the features of business promotion in social networks, describe the advantages and disadvantages of using social media. Key words: social networks, SMM, marketing, promotion in social networks, media.